Celecoxib in oncology: targeting the COX-2/PGE2 axis to reprogram the tumor immune microenvironment and enhance multimodal therapy - Kuang, Boyang; Yang, Kuan; Zhong, Xiaoting; Tan, Yingwei; Zhou, Yi; Ye, Jianming (Frontiers in Pharmacology, 2025)
Celecoxib, a selective cyclooxygenase-2 (COX-2) inhibitor, has emerged as a multifaceted therapeutic agent in oncology due to its dual anti-inflammatory and antitumor properties. This review synthesizes recent advances in understanding the molecular mechanisms and clinical applications of celecoxib in cancer treatment. Celecoxib not only hinders the proliferation and metastasis of tumor cells by inhibiting COX-2 synthesis, but also inhibits the intratumoral infiltration of regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs) and activates cytotoxic T cells, thereby reshaping the inhibitory immune microenvironment. Preclinical and clinical studies demonstrate its synergistic effects with chemotherapy, radiotherapy, and immunotherapy, particularly in augmenting immune checkpoint blockade efficacy. Despite the breakthrough of celecoxib in the field of oncology treatment, large-scale trials are warranted to validate its long-term safety and biomarker-driven accuracy. This work underscores the potential of celecoxib as a cornerstone in multimodal cancer therapy and provides a roadmap for its integration into personalized treatment paradigms.